Interactive methods in blended learning of the fundamentals of UI/UX design by pre-service specialists - Liudmyla Bilousova; Liudmyla Gryzun; Natalia Zhytienova (Academy of Cognitive and Natural Sciences, 2021)
The problems of blended learning implementation in the context of university students training in the subject domain of UI/UX design are discussed in the paper. Based on the literature review and educational practice analysis, it is revealed that the elaboration of the proper learning activities and methods is underestimated and overseen by the researchers and practitioners of blended learning implementation. It is admitted the urgency of finding out proper learning techniques (or their combination), which are necessary to involve the university students into interactive forms of work in order to overcome the core challenges of the blended learning implementation, and to add classroom atmosphere into the tutorial process in terms of online studying. In the progress of work, there were analyzed the core features and challenges of blended learning, and covered the possibilities of interactive methods in blended learning implementation into the tutorial process of students' mastering of UI/UX design basics, according to authors' approach to their curriculum building. The experience of interactive methods practical realization in the process of the fundamentals of UI/UX design learning by university students of different specialties is presented. It was demonstrated how the considered leaning techniques which are typically used at blended learning in its flex model (flipped learning, gamification, storytelling etc.) can be enhanced and enriched via using different interactive methods. Exact examples of their applications in real blended learning process are given and discussed. The prospects of the research are outlined.